Peningkatan Produktivitas Kopi Sistem Sambung Interspesifik Robusta/Liberika - Rusdi Evizal; Fembriarti Erry Prasmatiwi; Setyo Widagdo; Liska Mutiara Septiana (Universitas Lancang Kuning, 2022)
Lampung coffee farmers generally cultivate Robusta coffee and practice ethno-agronomy based on local wisdom, including cultivating coffee of Robusta/Liberica interspecific grafting system. This community service activity uses the method of face-to-face meetings, FGD, training, and making demonstration plots. The targets of this activity are management and members of Wijaya Muda farmer groups and farmers around the location at Pekon Sukajaya, Sumberjaya, West Lampung District.The results showed that based on evaluation results, the PKM activities was going well, with obtaining a total score of 12 (3 variables, scores 1-5) which indicated the level of participation was categorized as good. The evaluation of the results selected from 12 indicators of knowledge/skills showed an increase in the score of 53 to 73, which means that the level of knowledge skills increased from sufficient to good. The intensification of the Robusta/Liberica grafting system increased drought resistance and coffee production. Keywords: Biochar, grafting, interspesific, Robusta/Liberica, intensification